Subverting the strategic corporal: the IDF's contemporary heroic imagination. Issue 5 (3rd September 2021) - Stern, Nehemia
ABSTRACT: How does the Israel Defence Forces cultivate the image of a 'hero' within its combat ranks? By analysing a series of online educational videos on combat heritage, this article will demonstrate how the IDF's current heroic imagination is grounded in a subversion of the 'Strategic Corporal' paradigm. Within this paradigm, junior ranking soldiers are seen as increasing the chaos inherent in asymmetrical conflicts. By contrast, this article will argue that a focus on the learned elements of professionalism and training are seen as creating the conditions wherein every man (or woman) can become a 'hero'.